Research at Tribhuvan University, (T.U.): A Brief Appraisal of the State-of-the-art - Khatry, Prem (Tribhuvan University Journal, 2010)
Not available. Key words: State-of-the-art; Tribhuvan University; Nepal Tribhuvan University Journal Volume XVI, 1993 Page: 102-107 Uploaded date: 4 October, 2010